Hexa-substituted cyclotriphosphazene derivatives containing hetero-ring chalcones: Synthesis, in vitro cytotoxic activity and their DNA damage determination - Beytur, Asiye; Tekin, Cigdem; Caliskan, Eray; Tekin, Suat; Koran, Kenan; Gorgulu, Ahmet Orhan; Sandal, Suleyman (Academic Press Inc Elsevier Science, 2022)
In this study, hetero ring hexasubstituted cyclotriphosphazes were obtained in two steps and these compounds were investigated in terms of in vitro cytotoxicity and genotoxicity. The structural characterizations of the starting compounds 1-4 were defined by FT-IR, elemental analysis, and NMR (1H and 13C) spectroscopy techniques. In addition to these techniques, the 31P NMR spectroscopy technique was also used in the characterization of cyclotriphosphazenes (FSC 1-4). The changes in cell viability at 1, 5, 25, 50, and 100 mu M concentrations against human ovarian (A2780) and human prostate (PC-3 and LNCaP) cell lines for 24 h were determined by the MTT assay method. According to MTT assay results, the inhibitory concentration 50 (IC50/ LogIC50) value was calculated in Graphpad Prism 6 program. The comet assay was performed to determine whether the effects of compounds on cell viability were through DNA damage. In the comet assay experiments, the highest concentration of compounds (100 mu M) was applied to the cells for 24 h and tail length (TL), tail intensity (TI), olive tail moment (OTM) parameters were examined. The results showed that the compound 1-4 and FSC 1-4 compounds reduced the cell viability against all cancer cell lines (p < 0.05). At the same time, different concentrations of these compounds caused DNA damage in all three cell types (p < 0.05). The possible interactions and chemical mechanisms of the synthesized compounds were explained by computational methods with molecular docking. In addition, pharmacological properties of drug candidate molecules have been defined. Experimental and calculated data comply with each other. The study results showed that these compounds have cytotoxic effects against cancer cells and suggested that these effects have occurred through genotoxicity.
Keywords: Cyclotriphosphazene; Cytotoxicity; Genotoxicity; Chalcones; Synthesis